Single-cell transcriptomics reveals novel chondrocyte and osteoblast subtypes and their role in knee osteoarthritis pathogenesis - Yuan Liu; Wacili Da; Ming-Jie Xu; Chao-Xin Xiao; Tao Deng; Sheng-Liang Zhou; Xiao-Ting Chen; Yao-Jia Zhou; Li Tang; Yong Nie; Yi Zeng; Hui-Qi Xie; et al. (Signal Transduction and Targeted Therapy)
Abstract Research on treating knee osteoarthritis (KOA) is becoming more challenging due to a growing number of younger patients being affected. The pathogenesis of KOA is complex for being a multifactorial disease affecting the entire joint, with remodeling of subchondral bone playing a key role in the degeneration of the overlying cartilage. Therefore, this study constructed a bipedal postmenopausal KOA mouse model to better understand how the interplay between subchondral bone remodeling and cartilage degeneration contributes to KOA development. A single-cell atlas of the osteochondral composite tissue was established. Furthermore, three novel subtypes of chondrocytes, including Smoc2 + angiogenic chondrocytes, Angptl7 + angiogenic chondrocytes, and Col1a1 + osteogenic chondrocytes, were identified in femoral condyles of KOA mice. In addition, the Angptl7 + chondrocytes promoted angiogenesis in the subchondral bone of KOA mice by interacting with endothelial cells via the FGF2-FGFR2 signaling pathway. The number of H-type vessels was increased in the subchondral bone, recruiting osteoprogenitor cells and facilitating osteogenesis in KOA mice. Sparc + osteoblasts have negatively regulated bone mineralization and osteoblastic differentiation, aggravated the pathological remodeling of subchondral bone, and promoted the progression of KOA. The above findings have offered new targets and opened up an avenue for the therapeutic intervention of KOA.